Effect of decision to delivery interval on perinatal outcomes during emergency cesarean deliveries in Ethiopia: A prospective cohort study. - Tebabere Moltot Kitaw (Public Library of Science (PLoS), 2021)
Background The National guidelines of most developed countries suggest a target of 30 minutes of the decision to delivery interval for emergency cesarean section. Such guidelines may not be feasible in poorly resourced countries and busy obstetric settings. It is generally accepted that the decision to delivery interval should be kept to the minimum time achievable to prevent adverse outcomes. Therefore, this study aimed to determine the average decision to delivery interval and its effect on perinatal outcomes in emergency cesarean section. Methods A prospective cohort study was conducted from May to July 2020 at Bahir Dar City Public Hospitals. A total of 182 participants were enrolled, and data were collected using a structured and pre-tested questionnaire. A systematic sampling technique was applied to select the study subjects. Data were cleaned and entered into Epi-Data version 4.6 and exported to SPSS version 25 software for analysis. Logistic regression analysis was performed to identify predictors of outcome variables, and variables with a p-value of <0.05 were considered statistically significant. Results The average decision to delivery interval was 43.73 ±10.55 minutes. Anesthesia time [AOR = 2.1, 95%CI = (1.3-8.4)], and category of emergency cesarean section [AOR = 3, 95% CI = (2.1-11.5)] were predictors of decision to delivery interval. The prolonged decision to delivery interval had a statistically significant association with composite adverse perinatal outcomes (odds ratio [OR] = 1.8, 95% confidence interval [CI] = (1.2-6.5). Conclusion The average decision to delivery interval was longer than the recommended time. It should always be considered an important factor contributing to perinatal outcomes. Therefore, to prevent neonatal morbidity and mortality, a time-dependent action is needed.